The Meaning of Solidarity in News Songs to Friends: A Discourse Analysis Study - Leni Parwati; Henny Yusalia; Chairunnisah Putri Ayu Ningsih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Music is a form of communication that serves not only as entertainment but also as a means of conveying social messages, human values, and the realities of life through song lyrics. The song “Berita Kepada Kawan” by Ebiet G. Ade is one such song that depicts the suffering of victims of natural disasters as well as the values of solidarity, empathy, and sincerity. The purpose of this study is to analyze the solidarity depicted in the song “Berita Kepada Kawan” using Van Dijk’s discourse analysis model, which encompasses superstructural, microstructural, and macrostructural levels. This study employs a qualitative research method, and data collection was conducted through an analysis of the song’s lyrics as the primary data source. The focus of the analysis is to determine how the concept of solidarity is represented in the song through text structure, word choice, stylistic features, themes, and social context. The results of the study indicate that the lyrics of “Berita Kepada Kawan” represent solidarity by depicting the suffering of disaster victims, encouraging others to care, and reminding us of the importance of humanitarian values in society. It is hoped that this study will contribute to the development of communication studies, particularly discourse analysis, and broaden our understanding of music as an effective medium of communication for conveying social and humanitarian messages.